Role of Chlamydia pneumoniae in pediatric acute ischemic stroke: A hospital based study - Bandaru, V.C.S. Srinivasarao; Boddu, Demudu Babu; Singh, Vineeta; Akhila, Boddu; Laxmi, Vemu; Neeraja, Mamedi; Kumar, Bana Ashok; Reddy, Gunnamreddy Ramana; Jyotsna, Yarlagadda; Kaul, Subhash (Journal of Pediatric Neurology, 2010)
Several studies have shown that Chlamydia pneumoniae accelerates atherothrombosis by cytokine-mediated process with increased risk of cerebral ischemia in adults. Such a relationship has not been established in children. We sought to study the role of C. pneumoniae infection in children under the age of 18 years presenting with first ever-ischemic stroke. This study was carried out at a tertiary care hospital, between January 2006 and December 2008. Using a prospective registry, we enrolled all consecutive childhood stroke patients presenting within 72 h of stroke onset. All patients underwent neuroimaging tests as a part of their stroke work up. In addition to routine blood investigations, hypercoagulable panel and fasting lipid profile were estimated for all participants. We measured C. pneumoniae IgG and IgA antibodies, by microimmunofluorescence technique, for all participants. A total of 42 children under the age of 18 years who presented with acute ischemic stroke were studied. The mean age of presentation was 15.2 years and males outnumbered females by 5:2. Stroke risk factors were identified in 33 of 42 (80%) cases. C. pneumoniae seropositivity (IgG) was found in 14 of the 42 stroke patients. After adjustment in C. pneumoniae seropositive strokes, abnormal intima media thickness (odds ratio [OR]: 7.0; 95% confidence interval [CI]: 1.2–37.9), elevated total cholesterol (OR: 9.3; 95% CI: 1.6–53.2) and low-density lipoprotein cholesterol (OR: 27.0; 95% CI: 2.5–291.1) were significantly associated with ischemic stroke in children. C. pneumoniae infection is associated with atherogenic lipid profile in children presenting with acute ischemic stroke.
Keywords: Pediatric stroke; C. pneumoniae; intima media thickness; low-density lipoprotein cholesterol; total cholesterol